Primer group, kit and method for detecting hereditary deafness gene - WANG HUAWEN; GAN LIJIA; XU YANYAN; SUN MINGMING; HU CHANGMING; TANG ZHUJING (2024)
The invention discloses a primer group, a kit and a method for detecting hereditary deafness genes, 132 pairs of specific amplification primers are designed aiming at 256 variation sites of 38 deafness-related syndrome type and non-syndrome type genes, and a multiplex PCR (polymerase chain reaction) rapid library construction method is combined to detect the hereditary deafness genes. The requirements of rapidness, accuracy, high throughput and low cost of a hereditary deafness gene (variation sites on nuclear genomes and mitochondrial circular DNA) screening detection technology are met, and more comprehensive and more accurate detection is provided for subjects. 本发明公开了一种检测遗传性耳聋基因的引物组、试剂盒及方法，本发明针对38个耳聋相关综合征型和非综合征型基因的256个变异位点设计132对特异性扩增引物，并结合多重PCR快速构库方法，满足遗传性耳聋基因(核基因组及线粒体环状DNA上的变异位点)筛查检测技术快速、准确、高通量、低成本的要求，为受检者提供更全面、更精准的检测。